Project Based Learning Fosters Critical Thinking in Indonesian Language Classes: Pembelajaran Berbasis Proyek Meningkatkan Pemikiran Kritis dalam Kelas Bahasa Indonesia - Mellyta Wandha Chayaning; Nurdyansyah (Academia Open, 2025)
General Background: Critical thinking is an essential competency for elementary students in responding to real-life situations through reflective and analytical processes. Specific Background: In Indonesian elementary schools, learning practices often remain teacher-centered, limiting students’ opportunities to actively construct knowledge and develop higher-order thinking skills. Knowledge Gap: Previous studies on Project Based Learning have largely focused on subjects such as science and mathematics, while limited research examines its implementation in Indonesian language learning, particularly in poetry writing activities at the elementary level. Aims: This study aims to describe the implementation of Project Based Learning and to explain the role of teachers in developing sixth-grade students’ critical thinking skills in Indonesian language learning at SD Negeri 2 Sukobendu Lamongan. Results: Using a qualitative approach through observation, interviews, and documentation analyzed with data triangulation, the findings reveal that structured project phases—from formulating essential questions to reflection—encourage active participation, analytical thinking, evaluation, creativity, and communication skills. Poetry writing projects guided by teachers as facilitators and mentors support students in expressing experiences systematically and critically. Novelty: The study highlights the integration of Project Based Learning syntax with teacher multifaceted roles in Indonesian language instruction at the elementary level. Implications: The findings provide practical guidance for teachers in designing meaningful project-based activities to support sustainable development of critical thinking skills in primary education contexts. Keywords: Project Based Learning, Critical Thinking Skills, Teacher Role, Indonesian Language Learning, Elementary Education Key Findings Highlights: Structured project phases guide students from idea exploration to reflective evaluation in poetry writing activities. Teacher facilitation, mentoring, and feedback shape analytical reasoning and classroom participation. Learning contracts and presentation sessions support responsibility, collaboration, and self-assessment practices.